Indicadores de gestão para instituições de longa permanência para idosos: um estudo em uma entidade confessional - Lacerda, Cleber Colpes (Universidade do Vale do Rio dos Sinos, 2020)
This study has as main objective the construction of a structure of indicators to monitor, control and evaluate the management of assistance and financial economy within a Long Term Care Institution for the Elderly (ILPI) of a confessional entity, based on the best treatment and treatment practices. management. A change in the age profile of a society implies new challenges for public management, from the insertion of the theme that affects public policies to the implementation of preventive actions and targeted care as the requirements of the elderly. The proposed process aims to promote the structuring and continuous improvement of assistance to the elderly residents of the institution, supported by the theoretical framework and by the manager's experience. The chosen method was Design Science Research, which divides the design problem into practical and knowledge problems, aimed at building an artifact that offers the best solutions to existing problems. The present artifact aims to organize the components of the internal environment to achieve the goals established for the external environment. The model adopted and implemented contributes to promote changes in the administration of care for the elderly in LTCFs, facilitating the execution of activities, in addition to allowing access to the results achieved.
Keywords: Instituições de longa permanência; Idosos; Indicadores; Institutions of long stay; Elderly indicators; ACCNPQ::Ciências Sociais Aplicadas::Administração